Sport und Bewegung mit und nach Krebs – wer profitiert, was ist gesichert? - Steindorf, Karen; Schmidt, Martina E.; Zimmer, Philipp (DMW - Deutsche Medizinische Wochenschrift, 2018)
A growing number of literature reports positive effects of physical activity and exercise. These effects concern prevention, mortality and progress of cancer. Furthermore they show a reduction of disease- and treatment-specific side effects, which implies a better patients’ quality of life. Evidence shows a decreased mortality risk in patients with physically active cancer of colon, breast, ovaries and prostate. Activity recommendations for patients with cancer do not differ from those for healthy persons. However, a decrease in physical activity can be observed in many cancer patients after diagnosis, and this fact concludes to a reduced physical capacity – although just physical capacity helps to overcome the burden of medical treatment and to recover. In fact, tailored exercise programs can counteract a decrease in physical capacity successfully. Further they reduce side effects such as fatigue, incontinence and lymphedema. Moreover, first studies report a positive influence on: chemotherapy-induced polyneuropathies, cancer-related cognitive impairments, bone health and sleep. Finally, an enormous number of investigations showed that exercise interventions can improve psychosocial factors (e. g. mood and self-esteem). Except for very few conditions, such as extremely impaired blood cell counts and days when cardio- or nephrotoxic drugs are given, physical activity should be recommended. Especially during medical treatment, physicians and therapists are prompted to interact closely in order to prevent general activity prohibitions. Physical activity and exercise programs represent a unique and low-cost chance for cancer patients to influence the course of their own disease positively. More effort is necessary to improve professional activity offers for cancer patients and survivors and to specify activity recommendations.
Keywords: Sport; Bewegung; Krebs; Überleben; Nebenwirkungen